2015
DOI: 10.1016/j.actbio.2015.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interfacial interactions on deformation mechanism and interface viscosity in α-chitin–calcite interfaces

Abstract: The interfaces between organic and inorganic phases in natural materials have a significant effect on their mechanical properties. This work presents a quantification of the interface stress as a function of interface chemical changes (water, organic molecules) in chitin-calcite (CHI-CAL) interfaces using classical non-equilibrium molecular dynamics (NEMD) simulations and steered molecular dynamics (SMD) simulations. NEMD is used to investigate interface stress as a function of applied strain based on the viri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 71 publications
0
14
0
1
Order By: Relevance
“…The polymer chains in α‐chitin have an antiparallel arrangement ( Figure a), while β‐chitin have a parallel arrangement. γ‐chitin crystals have both parallel and antiparallel assemblies . In this review, we will focus on α‐chitin as it is the most abundant form found in Nature.…”
Section: Atomic Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The polymer chains in α‐chitin have an antiparallel arrangement ( Figure a), while β‐chitin have a parallel arrangement. γ‐chitin crystals have both parallel and antiparallel assemblies . In this review, we will focus on α‐chitin as it is the most abundant form found in Nature.…”
Section: Atomic Scalementioning
confidence: 99%
“…a) Structure of the chitin unit cell and molecular chains. Adapted with permission . Copyright 2015, Elsevier.…”
Section: Atomic Scalementioning
confidence: 99%
“…This difference in our results could be associated with the differences in the composition between the shrimp exoskeleton and the fungal cell wall. In studies carried out with ground and deep‐water shrimp, it was reported that the exoskeletons of both species possess the same microstructures: chitin, calcite, and other components, which are arranged in a helical structure in layers . In both cases, it is stated that the shrimp exoskeleton is hard and resistant, containing mainly chitin, proteins, and minerals; especially Ca, P, Na, and Zn.…”
Section: Resultsmentioning
confidence: 99%
“…The fibers, ordered in a laminated structure, are frequently reinforced by cross-linking with proteins, minerals, and waxes. Thus, they can be found in different shapes and functions as fungal cell walls, crustacean exoskeletons, insect cuticles, and butterfly wings ( Figure 4) [48,49]. However, alpha-chitin occurs in crustaceans in the predominant crystalline form with a polygonal section profile, consisting of 18-25 molecules with a diameter of 2 and 5 nm and lengths of about 300 nm [45][46][47][48][49].…”
Section: Chitinmentioning
confidence: 99%